An Analysis of the Effects of Brexit on Korean SMEs - kim, daejong (Archives of Business Research, 2018)
The purpose of this paper is to examine the impact on Korean SMEs after the Brexit . . The research method used an industry association analysis. The results of the study are as follows. First, total exports in 2015 were $ 519.9 billion, while exports to the UK were $ 7.4 billion. Exports to the UK are about 1.4% of Korea's total exports. The amount of damage to the total gross domestic product of Korea is estimated to be about 1.6 trillion won. SMEs account for about 56% of the total manufacturing output in Korea and about 12% of UK exports. Second, the loss estimate for SMEs is estimated to be W940bn. The amount of about 1 trillion won is a large amount, so anyone potentially affected will have to prepare. Policy implications are as follows: First, SMEs should move from export-oriented management to domestic-oriented management. Second, the export window should be unified to help SMEs export. The significance of this paper is to analyze the impact of small firms on SMEs.